Meta Analisis Pengaruh Iklim Kelas Terhadap Motivasi Belajar Siswa - Aqil Juniardi, Muhammad; Daniel; Rizqa, Miftahir (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Student learning motivation is influenced by the state of the classroom climate. This journal will discuss the meta-analysis of the effect of classroom climate on student learning motivation by comparing the correlation coefficient (r) values in existing research. This study aims to analyze the relationship between classroom climate and student learning motivation based on the grouping of correlation coefficient values consisting of very low, low, medium, strong, and very strong categories based on existing studies. The research carried out starts from the formulation of the topic of the problem, after which it compares the results of relevant research to be analyzed. Meanwhile, the method used is meta-analysis, which is a method that involves the use of secondary data from previous research results by searching journals through Research Gate and Google Scholar. Then proceed with analyzing the product-moment correlation category of the research results found based on the percentage presented in the form of a statistical diagram. From the search results, 12 journals were obtained, consisting of 3 international journals and 9 national journals. Based on the results of the meta-analysis, 34% of the journals showed a strong mutual influence relationship between classroom climate and student learning motivation. Building a conducive learning atmosphere is the responsibility of the teacher. With careful lesson planning, a comfortable physical classroom setting, and the creation of a positive socio-emotional climate, teachers can help students learn effectively and increase their motivation to learn so they can reach their full potential.